Study on the effect of dust exposure on the ventilatory function of the lung, among workers in ceramic factory in Petaling Jaya, Selangor, 1997 - Sadiah Abdullah,; Jamal Hisham Hashim, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study of the effect of dust exposure on 294 ceramic factory workers in Petaling Jaya, Selangor was carried out on January 1997.Questionare, physical examination, measurement of ventilatory function and respirable dust level were used in this study. The age of the worker were between 20 to 57 years old. The workers were divided into two groups according to exposures, the high. exposure and the low exposure group. Among the high exposure group 27% have abnormal lung ventilatory function compared to 20% among the low exposure group. The level of respirable dust and quartz was found to be significantly high in the factory areas, the concentration of respirable dust ,at the spraying area (42.27 mg/m3), compared to the level in the office ( 5.51mg/m3). The 'quartz' concentration was high at casting and spraying area (0.3 mg/m3) and exceeded the permissible level of the mineral regulation, The Factories and Machinery Act 1967. The ventilatory function of the lung of the workers was significantly lower than the predicted value p<0.05. The mean FEV1 was 2.61 ± 0.53 L while the predicted value was 2.92 ± 0.53 L. The mean FVC of the worker were slightly lower then the predicted value, where the mean FVC was 3.26 ± 0.6L while the mean predicted FVC was 3.31 ± 0.43 L. All the ventilatory functions were negatively correlated with duration of exposure. There were significant correlation between % FEV1/FVC and total exposure of dust and quartz, however there was no significant correlation with the pack year smoking. The height, age, race and sex are the main determinant of FEV1 and FVC. Symptoms of respiratory disorders are more frequent among the low dust exposure as there were high prevalence of bronchial asthma in this group. The prevalence of lung disorders among the workers of this ceramic factory are 7% for restrictive, 6.2% for obstructive and 0.7%for mixed lung disorders among the workers in this ceramic factory